Dynamic capabilities and the governance of energy resilience: Indonesia’s adaptive transition under the RUPTL 2025–2034 - Akhmad Feiral Rizky Batubara; John Tampil Purba (Jurnal Ekonomi Perusahaan, 2025)
This study analyzes how Indonesia governs energy resilience under the RUPTL 2025–2034 regulation during the country's adaptive transition using the dynamic capabilities approach. It investigates the operationalization of the sensing, seizing, and transforming capabilities, which are the flexible portion of the governance policy, organizational, and technological pillars in the adaptive transitions framework toward the envisioned sustainable energy future. Using strategic management and international case studies on energy transitions, this work highlights how Indonesia adjusts the adaptable and competitive components of its energy systems to respond to shifts in the global energy market. The dynamic capabilities and governance flexibility construct links energy resilience security and environmental sustainability, providing emerging economies valuable insights. Finally, the study emphasizes transition complexity and offers energy policy and energy transition managers concrete solutions.